2017
DOI: 10.17116/jnevro201711712225-33
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of homeostasis, inflammation and homocysteine in ischemic stroke in the young age

Abstract: The laboratory markers associated with cerebral thrombosis can be used for identification of a prothrombotic state as a cause of IS in the young age. Moderate hyperhomocysteinemia is a risk factor but not a cause of IS. The increase of inflammatory markers in APS suggests a role of infection in its development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The relation between elevated Hcy and neurovascular/neurodegenerative diseases has been established. Many mechanisms were proposed and studied for HHcy-induced vascular dysfunction, such as impaired endothelial function [65][66][67][68] oxidative stress [4,69,70], ER stress [71][72][73][74], inflammation [75][76][77][78][79], epigenetic modification [80][81][82][83], and activation of matrix metalloproteinase [84][85][86][87][88]. However, the exact mechanism of HHcy-induced vascular and barrier dysfunction is still undetermined.…”
Section: Mechanisms Of Homocysteine-induced Neurovascular/neurodegenerative Changes In the Central Nervous System (Cns)mentioning
confidence: 99%
“…The relation between elevated Hcy and neurovascular/neurodegenerative diseases has been established. Many mechanisms were proposed and studied for HHcy-induced vascular dysfunction, such as impaired endothelial function [65][66][67][68] oxidative stress [4,69,70], ER stress [71][72][73][74], inflammation [75][76][77][78][79], epigenetic modification [80][81][82][83], and activation of matrix metalloproteinase [84][85][86][87][88]. However, the exact mechanism of HHcy-induced vascular and barrier dysfunction is still undetermined.…”
Section: Mechanisms Of Homocysteine-induced Neurovascular/neurodegenerative Changes In the Central Nervous System (Cns)mentioning
confidence: 99%
“…[92][93][94][95] An association between elevated plasma homocysteine and the development of atherosclerosis has been confirmed. [96] Studies in animal models have shown that elevated homocysteine promoted atherosclerosis by increased oxidative stress impaired endothelial function and increased thrombogenecity. [92,93,[95][96][97][98][99] Epidemiological retrospective and prospective clinical studies established homocysteine as a potent independent risk factor for atherothrombotic vascular disease.…”
Section: Homocysteinementioning
confidence: 99%
“…[96] Studies in animal models have shown that elevated homocysteine promoted atherosclerosis by increased oxidative stress impaired endothelial function and increased thrombogenecity. [92,93,[95][96][97][98][99] Epidemiological retrospective and prospective clinical studies established homocysteine as a potent independent risk factor for atherothrombotic vascular disease. [91,92,100] Additionally, homocysteine increase superoxide (O 2 -) levels resulting in increased oxidative stress, causing an inflammatory state and increased atherosclerosis and ischemia reperfusion.…”
Section: Homocysteinementioning
confidence: 99%
See 2 more Smart Citations